Forgiveness therapy for the promotion of wellbeing: A systematic review and meta-analysis - Akhtar, S; Barlow, J (SAGE Publications, 2016)
Interpersonal hurts and violence against the individual have a high prevalence and are associated with a range of long-term problems in terms of psychological functioning. There is a growing body of research highlighting the role of forgiveness therapy in improving different aspects of psychological health in populations who have experienced diverse types of hurt, violence, or trauma. This article reports the findings of a systematic review and meta-analysis of the efficacy of process-based forgiveness interventions among samples of adolescents and adults who had experienced a range of sources of hurt or violence against them. Randomized controlled trials were retrieved using electronic databases and an examination of reference sections of previous reviews; each study was assessed for risk of bias. Standardized mean differences (SMDs) and confidence intervals (CIs) were used to assess treatment effects. The results suggest that forgiveness interventions are effective in reducing depression (SMD = −0.37, 95% CI [−0.68, −0.07]), anger and hostility (SMD = −0.49, 95% CI [−0.77, −0.22]), and stress and distress (SMD = −0.66, 95% CI [−0.91, −0.41]) and in promoting positive affect (SMD = −0.29, 95% CI [−0.52, −0.06]). There was also evidence of improvements in state (SMD = −0.55, 95% CI [−0.88, −0.21) and trait (SMD = −0.43, 95% CI [−0.67, −0.20]) forgiveness. The findings provide moderately strong evidence to suggest that forgiving a variety of real-life interpersonal offenses can be effective in promoting different dimensions of mental well-being. Further research is, however, needed.